The Importance of Freedom in Childhood in "The Anne with an E" Movie Series Season 1: Psychosocial Development Perspective - Lutfiyah, Luluk; Thoyibi, M. (Language Circle: Journal of Language and Literature, 2024)
Giving freedom to children is an issue that usually ignored until nowadays. People are not really aware how important give a freedom to children and affect their children’s character development.  Therefore, this research aims to analyze the indicators of the importance of freedom and impacts of freedom portrayed in the Anne with an E movie series, season 1. The following purpose of this research are: 1) To identify the indicators of the importance of freedom in the Anne with an E movie series, 2) To analyze how the importance of freedom depicted in the Anne with an E movie series, and 3) To reveal the reason why the importance of freedom is addressed in the Anne with an E movie series. The type of this study is a literary study, and the method of collecting data in this research are document and media analysis. While analyzing the data is used hermeneutic and note-taking for collecting data techniques. The results of this research are showing three indicators of the importance of freedom which can affect to their success through some stages of psychosocial development by Erikson’s theory. The depiction of freedom is depicted through characters, setting, events, and style.